Primary birthing attendants and birth outcomes in remote Inuit communities—a natural "experiment" in Nunavik, Canada. Issue 7 (13th March 2009) - Simonet, F; Wilkins, R; Labranche, E; Smylie, J; Heaman, M; Martens, P; Fraser, W D; Minich, K; Wu, Y; Carry, C; Luo, Z-C
Abstract : Background: There is a lack of data on the safety of midwife-led maternity care in remote or indigenous communities. In a de facto natural "experiment", birth outcomes were assessed by primary birthing attendant in two sets of remote Inuit communities. Methods: A geocoding-based retrospective birth cohort study in 14 Inuit communities of Nunavik, Canada, 1989–2000: primary birth attendants were Inuit midwives in the Hudson Bay (1529 Inuit births) vs western physicians in Ungava Bay communities (1197 Inuit births). The primary outcome was perinatal death. Secondary outcomes included stillbirth, neonatal death, post-neonatal death, preterm, small-for-gestational-age and low birthweight birth. Multilevel logistic regression was used to obtain the adjusted odds ratios (aOR) controlling for maternal age, marital status, parity, education, infant sex and plurality, community size and community-level random effects. Results: The aORs (95% confidence interval) for perinatal death comparing the Hudson Bay vs Ungava Bay communities were 1.29 (0.63 to 2.64) for all Inuit births and 1.13 (0.48 to 2.47) for Inuit births at ⩾28 weeks of gestation. There were no statistically significant differences in the crude or adjusted risks of any of the outcomes examined. Conclusion: Risks of perinatal death were somewhat but not significantly higher in the Hudson Bay communities with midwife-led maternity care compared with the Ungava Bay communities with physician-led maternity care. These findings are inconclusive, although the results excluding extremely preterm births are more reassuring concerning the safety of midwife-led maternity care in remote indigenous communities.